Criticism of the Concepts of Diversity and Inclusion in Western Countries - Steinmetz, Carl H. D. (Advances in Social Sciences Research Journal, 2021)
This article answers the question, "is the use of the words inclusion and diversity an expression of institutional racism?" In almost all Western countries, immigrants and refugees barely penetrate all levels of organizations. Immigrants and refugees are mostly found in the lower echelons of an organization. To put it irreverently: the dirtier and heavier the work, the more immigrants and refugees are found there. Also in governments and parliaments immigrants (not even the second, third and fourth generation) are hardly to be found. So the good example is lacking. This article starts with an etymological examination of inclusion and diversity. The outcome is briefly summarized: " we want YOU -immigrant and/or refugee- to come and work for us because we are not allowed to hire only natives". That human rights are violated in this way does not seem to be an issue. Furthermore, we argue that it is precisely the words inclusion and diversity that prevent the recruitment of immigrants and refugees, as well as expats who have lost their jobs, from being given a high priority. This article proposes two new terms as just and equitable alternatives to inclusion and diversity. First, the statistical concept of representative and second, in support of the static concept of representative, the concept of wanting to be a mirror of the population from the neighbourhood, city or country that the leadership of the company or institution believes should be part of the work organization and from low to high. To further support this argument to replace the concepts of inclusion and diversity, Moscovici's (2001) concept of social representation is used. This article also looks at existing toolboxes and toolkits that Western countries have developed to ensure that organizations of governments, institutions independent of government, and businesses are representative of neighbourhoods, cities, and countries. Companies in particular are committed to this because they understand better than anyone that their paying customers are also immigrants, refugees and expats. This knowledge of toolboxes and toolkits was helpful in developing a guideline for organizations of governments, institutions independent of government and companies and therefore also parliaments and governments. The guideline also addresses violations of this guideline. To address violations, it proposes a self-learning model for teams in organizations that is also consistent with enforcing the Working Conditions Act in Western countries.